Subcutaneous rather than intravenous ustekinumab induction is associated with comparable circulating drug levels and early clinical response: a pilot study. Issue 3 (19th June 2018) - Rowan, C. R.; Keegan, D.; Byrne, K.; Cullen, G.; Mulcahy, H. E.; Sheridan, J.; Ryan, E. J.; de Vries, A.; D'Haens, G.; Doherty, G. A.
Summary: Background: Ustekinumab (USK) is licenced for intravenous induction and subcutaneous (S/C) maintenance in Crohn's disease. Aim: To evaluate ustekinumab trough concentrations and clinical response with exclusive subcutaneous ustekinumab induction. Methods: Patients with Crohn's disease who initiated treatment with subcutaneous ustekinumab at a single academic centre were included in this pilot study. A dosage of 360 mg ustekinumab was given subcutaneously in divided doses; 180 mg at Week 0, 90 mg at Week 1 and 90 mg at Week 2, with corresponding ustekinumab trough concentrations assessed to Week 8. The primary outcome measures were trough serum ustekinumab levels and clinical remission at Week 8. Secondary outcome measures were trough serum ustekinumab levels at Week 1 & 2 and changes in C‐reactive protein, albumin and faecal calprotectin at Week 8. Results: Nineteen patients were included. Median Week 8 ustekinumab trough concentrations were 6.1 μg/mL (Inter‐quartile range 4‐9.8 μg/mL). There was a significant improvement in Harvey Bradshaw index from Week 0 (median HBI 5; interquartile range 2‐8) to Week 8 (median HBI 1; interquartile range 0‐3) ( P  = 0.002). C‐reactive protein levels did not change significantly but faecal calprotectin improved significantly; median faecal calprotectin at Week 0 was 533 μg/g; at Week 8, it was 278 μg/g ( P  = 0.038). Conclusions: Ustekinumab trough concentrations are comparable whether ustekinumab induction treatment was administered subcutaneously or intravenously. A significant improvement in symptoms and faecal calprotectin was noted. These results support the use of subcutaneous induction as an alternative if there are barriers to intravenous induction.